A systematic review of interventions to promote physical activity in six Gulf countries. - Elizabeth A Nash (Public Library of Science (PLoS), 2021)
Physical activity (PA) levels are low in Gulf Cooperation Council countries (GCC; Bahrain, Kuwait, Oman, Qatar, Saudi Arabia, United Arab Emirates). We carried out a systematic review (PROSPERO registration number 131817) to assess the effect of interventions to increase PA levels in this region. We also assessed their effects on anthropometry and cardiovascular risk. A systematic search of six databases (Medline, EMBASE, SPORTDiscus, CINAHL, Cochrane, Web of Science) was performed to identify randomized and non-randomized intervention studies performed in adults and children published between January 1985 and November 2020. We included studies published in English or Arabic, and included PA interventions regardless of setting, delivery, and duration. The primary outcomes were changes in PA duration and intensity. Secondary outcomes included anthropometric measures (e.g., weight, body mass index) and cardiovascular risk profiles (e.g., lipid measures, blood glucose). Two independent reviewers screened studies in accordance with pre-determined criteria, extracted data, assessed risk of bias (Cochrane Risk of Bias 2 and Newcastle Ottawa Scale) and undertook a narrative synthesis. From 13,026 records identified, 14 studies were included. Nine studies focussed exclusively on changing PA behaviour, resulting in statistically significant increases in step count ranging from an additional 757 steps/day (95% confidence interval [CI] 0-1,513) to 3,853 steps/day (95% CI 3,703-4,002). Five identified studies were multi-component lifestyle interventions, targeting people at higher risk (due to obesity or type 2 diabetes). Evidence for increases in PA from multi-component studies was limited, although improvements were seen in outcomes e.g. body weight and blood lipid levels. In conclusion, relatively few studies have focussed on changing PA behaviour, despite the urgent need in the GCC. Limited evidence suggested that pedometer-based programmes encouraging step counting and walking were effective in promoting PA, at least in the short term. Policies to roll out such interventions should be implemented and evaluated.